Voting intentions during the later stage of the COVID-19 pandemic: The roles of risk perception and performance evaluations in South Korea - Soo Yun Kim; Gyeongmin Kim; Seongoh Park; Cheonsoo Kim; Deok Hyun Jang; Dong-Hee Joe; Won Mo Jang (PLoS ONE, 2026)
In this study, we examine voting intentions during the later stage of the COVID-19 pandemic in relation to risk perceptions and performance evaluations. Although prior research has documented rally-around-the-flag effects during the early phase of the pandemic, less is known about how vote choice is structured once acute crisis conditions have waned. This study draws on a nationally representative survey conducted in South Korea around the March 2022 presidential election. The analysis examines associations between affective and cognitive risk perceptions, evaluations of the government’s COVID-19 countermeasures, overall government approval, economic evaluations and expectations, and voting intention. The results show that cognitive risk perception was associated with voting intention to a limited degree, whereas affective risk perception was not. More importantly, voting intentions were associated with conventional performance evaluations—overall government approval and economic evaluations and expectations—alongside pandemic-response approval, rather than being explained solely by the latter. This study addresses the need to better understand electoral behavior during the later phase of a prolonged crisis, a period that has received far less scholarly attention than the acute onset of the pandemic.